Análise da contribuição do programa de aprendizagem profissional do SENAC Canoas/RS para inserção do jovem no mercado de trabalho a partir do desenvolvimento de competências profissionais - Bitello, Luciane Amália (2013)
In Brazil the changes that have happened in economy and production process reflect on job offers in relation to the professional profile desired according to the labor force available on the market. Facing this scenery it is necessary to rethink the education focusing on the job market because the level of requirements have changed and indeed it is not enough to have a certificate to guarantee access and permanence in the job market. There are consequences for the employees who already have a placement in the job market and harder ones for youngsters at working age (from 16 years-old on) who face a dual uncomfortable situation for they do not have the experience or the wanted skills to get their first job. One of the alternatives that the government has found is invest in public policies to encourage the insertion of youngsters in the job market. Thinking of this matter this paperwork aims to analyze the Programa de Aprendizagem Profissional (Professional Learning Program) offered by SENAC for the development of professional competences in the insertion of youngsters in the job market in the Canoas, RS, outskirts. It also tries to analyze the different insights of the people that take part in the program. This paperwork is of qualitative and quantitative kind denominated study of case and counted on the participation of 204 subjects. The data collection took place from August to October 2012 through the use of quiz, semi-structured interview and document background. The data from interviewed people’s profile was analyzed and described in an absolute way whereas the data from the quizzes was regarded quantitatively through the Excel Software graphic and for last the descriptive answers from the quizzes were put together. While the information got from the interviews was analyzed using the technique of Contents Analysis suggested by Bardin. The study results show that (a) the guidelines in the Pedagogical Political Project partially guide the professors’ actions for the development of competences in the classroom; (b) the participation in the Learning Project helps in the development of behavioral competences for young drop-outs and students; (c) with the participation in the Learning Project 80% of students will have access to the first job; (d) the hiring companies usually get youngsters who show off at the Practice Step, through the evaluation of professional competences developed throughout the course.